Design and development of mechanically controlled above knee prosthesis / Md. Sayem Hossain Bhuiyan - Md. Sayem , Hossain Bhuiyan (2017)
A mechanically controlled prosthesis is designed and developed to enhance the controllability of the conventional passive type prosthesis within an affordable price. Unlike to the typical mechanical prosthesis, the new design has made the prosthesis to follow the residual limb movements without having any intricate guiding arrangement. A gear based knee joint has made the prosthesis to move according to the residual limb movement. A spring based ankle joint, on the other hand, helped the amputee to overcome the difficulties in producing required flexion and extension in their prosthetic feet. It also expedited the energy storing and returning quality of the prosthetic ankle. A torsion spring has enabled the ankle joint to rotate in a controlled way to any desired angle without demanding any additional setup. The gear based knee joint is designed to improve the performance of mechanical type above-knee prostheses. The gear set with some bracing, and bracket arrangement is used to enable the prosthesis to follow the residual limb movement. The proposed design of the ankle joint would enable the mechanical type ankle joint to overcome the limitation of stability, flexion and extension within an affordable price. This would enhance the range of motion of the mechanical type prosthesis without incorporating any expensive electronic devices into the ankle joint. Unlike the typical mechanical prosthesis, the new design would allow the prosthesis to bend forward and backward to any desired angle with enough stability. The pattern of the prosthetic gait cycle shows that the spring based ankle joint could imitate the movement of the prosthesis closely to the biological limb. The motion analysis and finite-element analysis (FEA) of knee joint and ankle joints components were carried out to assess the feasibility of the design. The FEA results were then compared with the real data obtained from the healthy subject. Stability analysis under disturbance and gait analysis during walking with the prosthesis was carried out to test the performance of the prosthesis. According to the simulation results, the patterns of kinematic and kinetic parameters profiles have shown a great resemblance with that of the gait cycle of a healthy biological limb. The factor of safety obtained from the stress analysis results of FEA was 3.5 and 4.9 for knee joint and ankle joint components respectively, which indicated to no possibility of design failure. From the performance analysis results, though the exact shape and amplitude of the motion analysis results were deviated 0.5 to 14 times than the healthy gait cycle data, the trend of the curves were still in good agreement. At dynamic platform setting, the overall postural stability was found to improve by 3.3 to 5 times, and fall risk was observed to increase by 1.2 to 3.3 times while using prosthesis; whereas at static platform setting, the postural stability and fall risk performances were found to decline by 1.3 times and by 1.8 times respectively. Finally, the cost of quasi-active type above knee prosthesis designed for a lower limb amputee was found considerably cheap and thus affordable for mass proportion of amputee.